2019
DOI: 10.1186/s40834-019-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation rates in a stair-step protocol with Letrozole vs clomiphene citrate in patients with polycystic ovarian syndrome

Abstract: PurposeTo compare ovulation rates between Letrozole and Clomiphene Citrate (CC) using a stair-step protocol to achieve ovulation induction in women with Polycystic Ovarian Syndrome (PCOS).MethodsThis is a retrospective cohort of predominantly Hispanic PCOS women of reproductive age who completed ovulation induction (OI) comparing women who underwent Letrozole stair-step protocol to those who underwent OI with CC stair-step. All women had a diagnosis of PCOS based on the 2003 Rotterdam criteria. For both protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Budinetz et al stated an increased risk of multiple pregnancies with the CC stair‐step protocol than the traditional regimen 23 . However, Thomas et al detected no multiple pregnancies in both LTZ and CC stair‐step groups 21 . In this study, no multiple pregnancies were observed in the LTZ stair‐step group, while two multiple pregnancies occurred in the CC stair‐step group ( p = 0.803).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Budinetz et al stated an increased risk of multiple pregnancies with the CC stair‐step protocol than the traditional regimen 23 . However, Thomas et al detected no multiple pregnancies in both LTZ and CC stair‐step groups 21 . In this study, no multiple pregnancies were observed in the LTZ stair‐step group, while two multiple pregnancies occurred in the CC stair‐step group ( p = 0.803).…”
Section: Discussioncontrasting
confidence: 52%
“…We calculated the sample size by using the G-Power version 3.1.9.4 (Universität Kiel, Germany), regarding the values indicated in the previous studies. 21 The minimum number of patients to be included in the study was 94, with a two-tailed alpha error of 0.05 and a power of 95%. Since 117 patients were included in our study, the power of the study was calculated as >95%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhancing the hypothalamic response, it increases the FSH sensitivity of the ovaries [ 44 ]. Due to its shorter half life, compared to CC, letrozole does not interfere with endometrial proliferation and reduces the occurrence of multiple pregnancies in ART protocols [ 45 , 46 ]. However, such use of letrozole is off label in many countries and concerns have been raised regarding possible negative fetal outcomes connected with its use, although such concerns are not supported by experimental evidence [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Ovulation inducing drugs such as letrozole and CC are the 1 st line choice of pharmacological agents used to induce ovulation and are administered at a dose of 2.5-7.5 mg/day beginning on 3-7 days and at dose of 50-150 mg/day beginning on 2-5 days of menstrual cycles respectively. 13,[20][21][22][23] Patients are said to have/be letrozole or CC failure or resistant when either letrozole or CC fail to result in pregnancy respectively. Synthetic or exogenous gonadotropins such as human chorionic gonadotropin or hCG are preferred 2 nd line choice of pharmacological agents in treating infertility when ovulation induction drugs fail and when a woman opts for IUI technique.…”
Section: Discussionmentioning
confidence: 99%
“…CC and letrozole either given alone or in combination with metformin or myo-inositol serves as the first line choice of treatment and has shown to have beneficial aspects in treating infertility. [20][21][22][23] Recombinant follicle stimulating hormone and human chorionic gonadotropin are the exogenous gonadotropins are preferred as second line choice of infertility treatment in PCOS women when treatment with ovulation induction drugs fail or in patients who ovulated but failed to conceive or in those women who are opting for IUI technique. 14 Intrauterine insemination or IUI also referred as artificial insemination is a technique used alone or in combination with ovulation inducing agents or gonadotropins.…”
mentioning
confidence: 99%